Binding power of Supreme Court resolutions in concreto in criminal cases (Discourse of Law and Administration, 2021)
The subject of the study is the problem of binding force of Supreme Court resolutions adopted in specific criminal cases. The legal basis for the adoption of these resolutions are the provisions of Article 441 of the Code of Criminal Procedure and Article 82 of the Act of 8 December 2017 on the Supreme Court. According to Article 441 § 1 of the Code of Criminal Procedure, if during the examination of an appeal an issue requiring a fundamental interpretation of the law arises, the appellate court may postpone the examination of the case and refer the legal issue for resolution to the Supreme Court, which may also refer the resolution of the legal issue to an enlarged panel of this court (arg. ex art. 441 § 2 of the Code of Criminal Procedure). The resolution of the Supreme Court is binding in the given case (arg. ex art. 441 § 3 of the Code of Criminal Procedure).  The provision of Article 82 of the Supreme Court Act concerns a situation where the Supreme Court, while examining a cassation appeal or other appeal, develops serious doubts as to the interpretation of the provisions of law constituting the basis for its decision, then it may postpone the examination of the case and present the legal issue for resolution to a panel of 7 judges of the court. The binding force of Supreme Court resolutions adopted under the above provision should be considered in terms of whether or not they have the force of a legal principle. Thus, when a Supreme Court resolution is given the force of a principle of law, it formally becomes binding within the Supreme Court, which means that it is binding on all the panels of the Supreme Court, including the full panel of the Supreme Court.
Keywords: Supreme Court; binding force of Supreme Court resolutions; requiring fundamental interpretation of a statute